Strategi Guru dalam Meningkatkan Pencapaian Nilai KKM Mata Pelajaran PAI Siswa Kelas IX di SMPN 1 Kotabaru Kabupaten Karawang - Siti Sarah; Nan Rahminawati; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. One of the factors that influence the success of learning in terms of teachers is strategy. A learning course has an assessment that has special limitations that have been set by a teacher. These limits are known as the Minimum Completeness Criteria (KKM). This research is an empirical research using qualitative descriptive method. This study uses a theoretical and empirical study presented in the form of a narrative text to explain clearly how the teacher's strategy in improving the achievement of KKM PAI scores for grade IX students at SMPN 1 Kotabaru, Karawang district. Data collection techniques in this study used the methods of observation, interviews, and documentation. The results of the study indicate that: (a) There are six steps the teacher takes in increasing the achievement of students' KKM scores, namely by preparing teaching, choosing learning methods, choosing learning techniques, approaching students, providing learning motivation, and using learning media. (b) The method used by the teacher in increasing the achievement of students' KKM scores is a learning method that has been selected and adapted to the learning material. (c) The technique used by the teacher in increasing the achievement of students' KKM scores is a learning technique that has been selected and adapted to the material to support the strategies and learning methods used. Abstrak. Salah satu faktor yang mempengaruhi keberhasilan pembelajaran dari segi guru adalah strategi. Suatu pembelajaran tentunya ada penilaian yang memiliki batasan-batasan khusus yang telah ditetapkan oleh seorang guru. Batasan tersebut adalah Kriteria Ketuntasan Minimal (KKM). Penelitian ini merupakan penelitian empirik dengan menggunakan metode deskriptif kualitatif. Penelitian ini menggunakan kajian teoritis dan empiris yang disajikan dalam bentuk teks yang bersifat naratif untuk memaparkan secara jelas bagaimana strategi guru dalam meningkatkan pencapaian nilai KKM PAI siswa kelas IX di SMPN 1 Kotabaru kabupaten Karawang. Teknik pengumpulan data dalam penelitian ini menggunakan metode observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa: (a) Terdapat enam langkah guru dalam meningkatkan pencapaian nilai KKM siswa yaitu dengan melakukan persiapan pengajaran, memilih metode pembelajaran, memilih teknik pembelajaran, melakukan pendekatan terhadap siswa, memberikan motivasi belajar, serta menggunakan media pembelajaran. (b) Metode yang digunakan oleh guru dalam meningkatkan pencapaian nilai KKM siswa adalah metode pembelajaran yang telah dipilih dan disesuaikan dengan materi pembelajaran. (c) Teknik yang digunakan oleh guru dalam meningkatkan pencapaian nilai KKM siswa adalah teknik pembelajaran yang telah dipilih dan disesuaikan dengan materi demi mendukung strategi dan metode pembelajaran yang digunakan.